The Impact of the COVID-19 Pandemic on Dental Education in the Czech Republic: Students' Perception of Hybrid Clinical Education and Psychosocial Impacts, a Retrospective Study - Vavřičková, Lenka; Schmidt, Jan; Slezák, Radovan; Čermáková, Eva; Micopulos, Christos; Malíková, Bára; Kapitán, Martin (Prague medical report, 2024)
The COVID-19 pandemic significantly impacted educational methods worldwide, particularly in dental and general medicine education. This study retrospectively analyzes students' perceptions of hybrid theoretical and practical teaching in the Dentistry program during the pandemic at three medical faculties of Charles University in the Czech Republic. A total of 418 students were surveyed regarding their views on hybrid education, concerns about COVID-19, and the pandemic's psychosocial and academic effects. The study revealed notable differences based on faculty location, gender, year of study, language of instruction, and the phase of study affected. Students from smaller faculties (Hradec Kralove and Pilsen) preferred online education and did not report a significant reduction in lectures. Compensatory block teaching post-pandemic was effective but less preferred, especially among women. Men found online communication more challenging than women. Czech-speaking students rated online teaching more effective than those studying in English and compensated for clinical skill gaps by participating in more internships. Future online education methods should address the unique needs of these groups.
Keywords: studenti stomatologie; COVID-19 pandemic; Pandemics; Retrospective Studies; SARS-CoV-2; Česká republika; Students’ perception; průzkumy a dotazníky; mužské pohlaví; COVID-19; Education, Dental; Dental education; Adult; Czech Republic; ženské pohlaví; studium stomatologie; retrospektivní studie; Humans; distanční studium; Charles University; Surveys and Questionnaires; Online; Education, Distance; dospělí; pandemie; Female; Students, Dental; lidé; Male